The family in the health-illness process: A case analysis (2020)
Objective: To interpret family dynamics and its influence on health-disease processes under the approach of health promotion. Methods: Qualitative analysis based on the study of a family case obtained through field records and family records of the Los Patriotas neighborhood, in the city of Tunja, Boyacá, during the year 2019. Results and conclusions: The family, as a system, is a group of individuals who have dynamic relationships with each other, and whose positive or negative events can affect different areas, among them, the health-disease process. The family and the community present aspects that enrich the understanding of the family physician in situations related to the social determinants of health and primary health care; their practice and their relationship with the community, institutional and cultural environments allow a better understanding of the family as a system, and, in this way, of the history of the disease or of the basic criteria of health.